Impact of professionalism in nursing on in‐hospital bedside monitoring practice. (27th August 2012) - Bunkenborg, Gitte; Samuelson, Karin; Åkeson, Jonas; Poulsen, Ingrid
Abstract: Aim: This article reports a study exploring nursing practice of monitoring in‐hospital patients including intra‐ and interprofessional communication and collaboration. Background: Sub‐optimal care in general in‐hospital wards may lead to admission for intensive care, cardiac arrest, or sudden death. Reasons may include infrequent measurements of vital parameters, insufficient knowledge of their predictive values, and/or sub‐optimal use of Medical Emergency Teams. This study was designed to improve understanding of nursing practice and to identify changes required to support nursing staff in improving standards of clinical monitoring practice and patient safety in general in‐hospital wards. Design: The study was designed as a qualitative descriptive clinical study, based on method triangulation including structured individual observations and semi‐structured individual interviews. Methods: In the spring of 2009, structured observations and semi‐structured interviews of 13 nurses were carried out at a university hospital in Copenhagen, Denmark. The observational notes and interview transcriptions were analysed using content analysis. Results: One theme (Professionalism influences nursing monitoring practice) and two sub‐themes (Knowledge and skills and Involvement in clinical practice through reflections) were identified. Three categories (Decision‐making, Sharing of knowledge, and Intra‐ and interprofessional interaction) were found to be associated with the theme, the sub‐themes, and with each other. Conclusion: Clinical monitoring practice varies considerably between nurses with different individual levels of professionalism. Future initiatives to improve patient safety by further developing professionalism among nurses need to embrace individual and organizational attributes to strengthen their practice of in‐hospital patient monitoring and management.